2014
DOI: 10.1063/1.4904861
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen annealing on the multiferroic properties of Ca2+ doped BiFeO3 nanoceramics

Abstract: The high leakage current in divalent ion doped BiFeO 3 systems is limiting their large scale application. It is clearly shown that the methodology of oxygen annealing will prove to be an effective procedure for suppressing the detrimental consequences that originate from the oxygen vacancies. The samples annealed under oxygen also show different particle morphologies and packing density that can help in tuning the relevant physical properties, viz., magnetic, ferroelectric, and magnetoelectric. The difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Where, A is pre-exponential factor and n (1>n>0) determines the departure from ideal capacitor (Debye behavior). For n=0, Q behaves perfectly resistive and for n=1, it behaves as an ideal capacitor [23]. The simulation clearly indicates the presence of two relaxations.…”
Section: Relaxation Behavior and Electrical Propertiesmentioning
confidence: 81%
See 1 more Smart Citation
“…Where, A is pre-exponential factor and n (1>n>0) determines the departure from ideal capacitor (Debye behavior). For n=0, Q behaves perfectly resistive and for n=1, it behaves as an ideal capacitor [23]. The simulation clearly indicates the presence of two relaxations.…”
Section: Relaxation Behavior and Electrical Propertiesmentioning
confidence: 81%
“…4(b). C is the capacitance, R is the resistance and Q is the constant phase element (CPE) which is the modified capacitance of BLTFN ceramics having impedance Z* CPE =[A(jω) n ] -1 [23]. Where, A is pre-exponential factor and n (1>n>0) determines the departure from ideal capacitor (Debye behavior).…”
Section: Relaxation Behavior and Electrical Propertiesmentioning
confidence: 99%
“…Where R and C are the resistance and capacitance of the elements, respectively, and Q is the constant phase element (CPE) of the circuit. CPE represents the modified capacitance of the ceramics materials having impedance Z* CPE = [ A (j ω ) n ] −1 . In the equation, A is pre‐exponential factor and n is the empirical exponent, indicates the departure from Debye behavior and its values varies from 0 to 1; Q perform as perfect resistive nature for n=0 and operate as an ideal capacitor for n=1 .…”
Section: Resultsmentioning
confidence: 99%
“…44 In the equation, A is pre-exponential factor and n is the empirical exponent, indicates the departure from Debye behavior and its values varies from 0 to 1; Q perform as perfect resistive nature for n=0 and operate as an ideal capacitor for n=1. 44 What is the main contribution to the single relaxation, grains or grain boundaries or simply the bulk? As known that complex impedance data only highlight the more dominant resistive element of the microstructural components, 45 therefore, the only interpretation of complex impedance data is insufficient for the correct understanding of relaxation behaviors in BTFT ceramics.…”
Section: Complex Impedance Spectroscopymentioning
confidence: 99%
“…The idea was to examine the effect of introduction of anion vacancies on the lattice, already bestowed with high mobility of oxide ions, on the ionic conductivity. The presence of oxygen vacancies, in general, is known to possess a great influence over the response of the material to electrical stimuli [10]. Recently several studies on ionic conductivity behavior of ceria based mixed oxides have been reported [11][12][13].…”
Section: Introductionmentioning
confidence: 99%